The endophytic fungus Piriformospora indica protects wheat from fusarium crown rot disease in simulated UK autumn conditions. (8th January 2015) - Rabiey, M.; Ullah, I.; Shaw, M. W.
Abstract : The root endophytic fungus Piriformospora indica (Sebacinacea) forms mutualistic symbioses with a broad range of host plants, increasing their biomass production and resistance to fungal pathogens. This study evaluated the effect of P. indica on fusarium crown rot disease of wheat, under in vitro and glasshouse conditions. Interaction of P. indica and Fusarium isolates under axenic culture conditions indicated no direct antagonistic activity of P. indica against Fusarium isolates. Seedlings of wheat were inoculated with P. indica and pathogenic Fusarium culmorum or F. graminearum and grown in sterilized soil‐free medium or in a non‐sterilized mix of soil and sand. Fusarium alone reduced emergence and led to visible browning and reduced root growth. Roots of seedlings in pots inoculated with both Fusarium isolates and P. indica were free of visible symptoms; seed emergence and root biomass were equivalent to the uninoculated. DNA was quantified by real‐time polymerase chain reaction (qPCR). The ratio of Fusarium DNA to wheat DNA rose rapidly in the plants inoculated with Fusarium alone; isolates and species were not significantly different. Piriformospora indica inoculation reduced the ratio of Fusarium to host DNA in the root systems. The reduction increased with time. The ratio of P. indica to wheat DNA initially rose but then declined in root systems without Fusarium . With Fusarium, the ratio rose throughout the experiment. The absolute amount of Fusarium DNA in root systems increased in the absence of P. indica but was static in plants co‐inoculated with P. indica .